Assessment of Physical and Emotional Wellbeing of Medical Students using SF-36 Questionnaire - Shehnaz Khan, Zain Iftikhar, Zahra Shehzad, Umama Rehman, Sawera Ayub, Urooj Zulfiqar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The pressures of medical school can be extremely difficult for personal wellness and contribute to anxiety, burnout and depression. High demands for academic performance and restraints of extracurricular activities all add to distress of a medical student. Methodology: A cross sectional study using convenient sampling was carried out in medical students of CPMC, Lahore. A sample size of 208 was taken. The data was collected using the SF-36 questionnaire. Data was presented as percentages, frequencies, mean and standard deviation. Results: The mean score of physical activity was 61.35+27.02 SD. The average score of restraints due to physical health and hindrance due to emotional health was 38.58+37.49 SD and 34.26+15.37 SD. The mean score of discomfort was 59.57+27.70 SD. The Mean+SD of the score for vitality or tiredness was 46.47+16.69 SD. The average score of emotional health, social relationships and general fitness was 51.10+16.64 SD, 52.82+21.57 SD and 54.04+18.76 SD. Practical implication of the study is to observe the physical and emotional health of students enrolled in MBBS program. Conclusion: The questionnaire SF-36 has been used in the past literature for the assessment of physical and emotional well-being of patients suffering from any particular disease. We observed that the female participants had poor physical and emotional health compared to male participants. Keywords: Mental, physical, medical students, assessment.